Exploring EFL Students’ Perceptions of LMS-Based English Learning Through the Technology Acceptance Model - Ariya Agustin (LIMEEMAS: Jurnal Ilmiah Pendidikan, 2025)
The integration of Learning Management Systems (LMS) has become increasingly prominent in English as a Foreign Language (EFL) instruction in higher education. This study aims to explore EFL students’ perceptions of LMS-based English learning through the Technology Acceptance Model (TAM). A quantitative descriptive approach was employed, involving undergraduate students enrolled in English courses at a higher education institution. Data were collected using a questionnaire that measured key TAM constructs: perceived ease of use, perceived usefulness, attitude toward using, and behavioral intention to use the LMS. The data were analyzed using descriptive statistics and correlation analysis. The findings reveal that students hold positive perceptions of LMS-based English learning, with high perceived usefulness and ease of use. These perceptions significantly contribute to positive attitudes and strong intentions to continue using an LMS for English learning. The results also indicate that LMS supports flexible access to learning materials, enhances student engagement, and facilitates independent learning. This study confirms the relevance of TAM in understanding technology acceptance in EFL contexts and underscores the importance of integrating pedagogically sound LMS design in language instruction. The findings provide valuable implications for educators and institutions in optimizing LMS implementation to support effective English language learning in higher education.